2017
DOI: 10.1002/hed.24931
|View full text |Cite
|
Sign up to set email alerts
|

Complications and donor site morbidity of 3‐layer reconstruction with iliotibial tract of the anterior skull base: Retrospective analysis of 186 patients

Abstract: Background: Anterior skull base reconstruction after resection of sinonasal cancers may be challenging when pedicled flaps are unavailable. The purpose of the present study was to analyze the complication rate and donor site morbidity of 3-layer reconstruction with the iliotibial tract (ITT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…23,26 Earlier studies on fascia lata complications for ptosis surgery, which is obviously achieved with smaller graft size, found lower satisfaction in the first week, which improved with time. 21,22 In our cohort of patients, 21.8% (n ¼ 26) had early, and 12.6% (n ¼ 15) had late CNS complications, and these rates are also similar to large published studies. 10,11 In an effort to identify the patients who had early CNS complications after fascia lata reconstruction, our univariate and multivariate analyses found that malignant histology and the use of continuous lumbar drainage were predictors for CNS complications.…”
Section: Discussionsupporting
confidence: 89%
“…23,26 Earlier studies on fascia lata complications for ptosis surgery, which is obviously achieved with smaller graft size, found lower satisfaction in the first week, which improved with time. 21,22 In our cohort of patients, 21.8% (n ¼ 26) had early, and 12.6% (n ¼ 15) had late CNS complications, and these rates are also similar to large published studies. 10,11 In an effort to identify the patients who had early CNS complications after fascia lata reconstruction, our univariate and multivariate analyses found that malignant histology and the use of continuous lumbar drainage were predictors for CNS complications.…”
Section: Discussionsupporting
confidence: 89%
“…More convincing evidence of the potential efficacy of free graft reconstruction techniques is provided by a recent study published by Matavelli et al, wherein the authors describe the results following the resection of 186 sinonasal malignancies, resulting in large anterior cranial fossa defects. Using autologous iliotibial tract and fat tissue in a three-layer reconstruction protocol, the authors reported a post-operative CSF leak rate of 5.8% (47). Although these studies do suggest that acceptable results can be obtained with the use of free graft techniques, in the absence of a trial comparing both techniques, the weight of the evidence suggests that lower rates of CSF leak are obtained with the use of local vascularized flaps, and this view is supported by the results of a systematic review comparing the efficacy of skull base reconstruction methods following EEA (48).…”
Section: Alternative Optionsmentioning
confidence: 99%
“…An I 2 value of 0% indicated no heterogeneity, while values less than 50% indicated low heterogeneity, values less than 75% indicated moderate heterogeneity and values above 75% indicated substantial heterogeneity. Egger's test and funnel plots were used to view (14) Flap Retrospective 7 8 238 2009-2017 Zwagerman (4) LD RCT Low 25 170 2011-2015 Kuan (15) Flap Retrospective 6 7 300 2013-2016 Caggiano (16) Obesity, LD , RTx Retrospective 8 18 811 2008-2017 Conger (10) Flap Retrospective 7 9 551 2010-2017 Turri-Zanoni (6) Flap, RTx, size Retrospective 9 26 513 1998-2017 Ben-Ari (17) LD, sella Retrospective 7 1 12 2011-2016 Patel (18) Flap, RTx Retrospective 8 38 806 2004-2016 Kutlay (19) TC Retrospective 5 9 106 2010-2017 Mattavelli (20) RTx Retrospective 9 11 186 2007-2015 Jeon (21) Flap, TC Retrospective 8 14 95 2009-2014 Patel (22) Obesity, flap Retrospective 7 3 16 1995-2016 Fraser (3) Obesity, flap, LD, Retrospective 8 103 615 1997-2012 Stapleton (9) Obesity, flap, sella, TC Retrospective 7 11 47 1999-2014 Shahangian (23) Flap, LD, RTx Retrospective, multicenter 9 112 2097 2002-2014 Fathalla (24) Size, sella, TC, FR Retrospective 7 4 84 1999-2014 Dolci (25) FR, sella Retrospective 7 3 40 2012-2014 Karnezis (26) Flap, LD, RTx, sella, FR Retrospective 8 68 1161 2002-2014 Roxbury (27) Obesity, FR Retrospective 6 5 73 2008-2014 Thomas (28) FR, sella Retrospective 7 6 43 2011-2015 Dehdashti (29) FR Retrospective 8 11 180 2009-2013 Nix (30) FR, sella, TC Retrospective 8 10 51 2009-2015 Horiguchi …”
Section: Statisticsmentioning
confidence: 99%